Long ester chain thiophene copolymer as well as preparation method and application thereof

By using long-ester chain thiophene copolymer as the hole transport layer material, the problem of improving the energy conversion efficiency of perovskite solar cells in the prior art is solved, and the effect of maintaining high efficiency and stability in long-term use is achieved.

CN119529248APending Publication Date: 2025-02-28CHAIN WALKING NEW MATERIAL TECHNOLOGY (GUANGZHOU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411820450.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In the prior art, when improving the energy conversion efficiency of perovskite solar cells, it is difficult to maintain a high variable output circuit voltage and short-circuit current density at the same time, and P3HT as a material of the hole transport layer leads to poor stability, resulting in a decrease in energy conversion efficiency during long-term use.

Method used

Long-ester chain thiophene copolymers are used, specifically copolymers of 3-hexylthiophene and 3-(2-undecyloxyethyl)thiophene, in which the 3-(2-undecyloxyethyl)thiophene segment accounts for 5-15% of the molar percentage of the copolymer segment to improve the fill factor and enhance the stability of the material.

Benefits of technology

While maintaining a high variable output circuit voltage and short-circuit current density, the filling factor is improved, thereby significantly improving the energy conversion efficiency of perovskite solar cells and maintaining stability during long-term use, so that the unpackaged solar cells remain stable in the atmospheric environment for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a long ester chain thiophene copolymer and a preparation method and application thereof, the long ester chain thiophene copolymer is a copolymer of 3-hexylthiophene and 3-(2-undecane acyloxy ethyl) thiophene, and the 3-(2-undecane acyloxy ethyl) thiophene chain segment accounts for 5-15 mol% of the long ester chain thiophene copolymer chain segment; when the copolymer is applied to preparation of the perovskite solar cell, a fill factor can be improved under the condition of maintaining relatively high variable output circuit voltage and short-circuit current density, so that the energy conversion efficiency can be effectively improved, and the perovskite solar cell can maintain relatively high energy conversion efficiency in a long-term use process; therefore, the unpackaged perovskite solar cell can keep stable for a long time in the atmospheric environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thiophene copolymers, and in particular to a long ester chain thiophene copolymer and a preparation method and application thereof. Background Art

[0002] Solar cells are a well-known green new energy source. The power conversion efficiency (PCEs) of single-junction perovskite solar cells (PSCs) has reached 26%. Due to their low-cost manufacturing process and impressive photoelectric performance, perovskite solar cells are considered to be an important resource for the next generation of photovoltaic cells.

[0003] Perovskite solar cells generally include a fluorine-doped tin oxide layer (FTO) conductive substrate, an electron transport layer, a perovskite photosensitive layer, a hole transport layer and a counter electrode. For perovskite solar cells, in order for the photogenerated holes to be transported from the perovskite layer to the back electrode via the hole transport layer, the HOMO energy level of the hole transport material must be between the perovskite layer and the back electrode.

[0004] The material of the hole transport layer is one of the important factors that determine the energy conversion efficiency of perovskite solar cells. Among them, P3HT is a more commonly used material for the hole transport layer, but P3HT has a higher highest occupied molecular orbital (HOMO) energy level (-4.90eV), which causes the solar cell based on P3HT to often have a lower variable output circuit voltage, limiting the further improvement of its energy conversion efficiency. In order to improve the problem that P3HT as a material for the hole transport layer causes the perovskite solar cell to have a lower variable output circuit voltage, the prior art generally uses other monomers to copolymerize with 3-hexylthiophene to obtain a P3HT copolymer, thereby increasing the variable output circuit voltage of the perovskite solar cell. For example, CN119019651A discloses an ester-thiophene-hexylthiophene copolymer and its preparation method and application, by copolymerizing 3-(2-acetoxyethyl)thiophene or 3-(2-acetoxymethyl)thiophene with 3-hexylthiophene to obtain an ester-thiophene-hexylthiophene copolymer, thereby increasing the variable output circuit voltage of the perovskite solar cell. For another example: CN110218298B discloses three block copolymers of poly(3-heptylthiophene / 3-hexylthiophene), poly(3-heptylthiophene / monomethyl ether triethoxythiophene) and poly(3-heptylthiophene / 3-hexylthiophene / monomethyl ether triethoxythiophene). Heptyloxy, hexyl, etc. can be introduced into the side groups of the copolymers to effectively improve the variable output circuit voltage and short-circuit current density of the perovskite solar cell. It can be seen that the existing technology for improving the energy conversion efficiency (PCE) is mostly through increasing the short-circuit current density (Jsc) or the variable output circuit voltage, but it is difficult to improve the fill factor (FF), and thus it is difficult to significantly improve the energy conversion efficiency. Therefore, how to improve the fill factor while maintaining a relatively high variable output circuit voltage and short-circuit current density is an urgent problem to be solved.

[0005] In addition to the problem that using P3HT as a hole transport layer material will cause perovskite solar cells to have a lower variable output circuit voltage, using P3HT as a hole transport layer material in perovskite cells also has the problem of poor stability, which in turn causes the energy conversion efficiency of perovskite solar cells to decrease during long-term use. How to make perovskite solar cells maintain a high energy conversion efficiency during long-term use is also an urgent problem that needs to be solved. Summary of the invention

[0006] The object of the present invention is to overcome the defects and shortcomings of the prior art and to provide a long ester chain thiophene copolymer, which has better solubility and processing performance, more controllable molecular weight and regularity, and can improve the fill factor while maintaining a relatively high variable output circuit voltage and short-circuit current density, thereby effectively improving the energy conversion efficiency. Because of the ability of the long ester chain to block water vapor, the unpackaged perovskite solar cell can also maintain stability for a long time in the atmospheric environment, thereby enabling the perovskite solar cell to maintain a relatively high energy conversion efficiency during long-term use.

[0007] The object of the present invention is to provide a long ester chain thiophene copolymer, which is a copolymer of 3-hexylthiophene and 3-(2-undecanoyloxyethyl)thiophene, and the molar percentage of the 3-(2-undecanoyloxyethyl)thiophene chain segment in the long ester chain thiophene copolymer chain segment is 5-15%.

[0008] In some embodiments of the present invention, the molar percentage of the 3-(2-undecanoyloxyethyl)thiophene chain segment in the long ester chain thiophene copolymer chain segment is 5-10%.

[0009] In some embodiments of the present invention, the molar percentage of the 3-(2-undecanoyloxyethyl)thiophene chain segment in the long ester chain thiophene copolymer chain segment is 12-15%.

[0010] In some embodiments of the present invention, the long ester chain thiophene copolymer is a random copolymer.

[0011] In some embodiments of the present invention, the structure of the long ester chain thiophene copolymer is shown in formula (I):

[0012]

[0013] Formula (I)

[0014] Wherein, the number average molecular weight of the long ester chain thiophene copolymer is 9.7~17.3KDa.

[0015] In some embodiments of the present invention, the structure of the long ester chain thiophene copolymer is shown in formula (I):

[0016]

[0017] Formula (I)

[0018] Wherein, the number average molecular weight of the long ester chain thiophene copolymer is 12.7~13.3KDa.

[0019] In some embodiments of the present invention, the HT value of the long ester chain thiophene copolymer is ≥80%, and the PDI is ≥3.5.

[0020] Another object of the present invention is to provide a method for preparing a long ester chain thiophene copolymer, comprising the following steps:

[0021] Under the catalysis of palladium catalyst, 2-bromo-3-(2-undecanoyloxyethyl)thiophene and 2-bromo-3-hexylthiophene react to obtain the long ester chain thiophene copolymer.

[0022] In some embodiments of the present invention, the palladium catalyst is selected from a quinoline imine palladium catalyst, and the structure of the quinoline imine palladium catalyst is shown in formula (II):

[0023] .

[0024] Formula (II)

[0025] In some embodiments of the present invention, the molar ratio of 2-bromo-3-(2-undecanoyloxyethyl)thiophene to 2-bromo-3-hexylthiophene is 1-3:7-9.

[0026] In some embodiments of the present invention, the ratio of the total mole of 2-bromo-3-(2-undecanoyloxyethyl)thiophene and 2-bromo-3-hexylthiophene to the mole of the palladium catalyst is 1:0.001-0.05.

[0027] In some embodiments of the present invention, the reaction temperature is 90-130° C. and the reaction time is 12-48 hours.

[0028] In some embodiments of the present invention, the reaction further comprises an inorganic base, an organic acid and a solvent; the inorganic base comprises at least one of potassium carbonate and sodium carbonate.

[0029] In some embodiments of the present invention, the organic acid includes at least one of pivalic acid and caproic acid.

[0030] In some embodiments of the present invention, the solvent includes N,N-dimethylacetamide.

[0031] In some embodiments of the present invention, the ratio of the total mole of 2-bromo-3-(2-undecanoyloxyethyl)thiophene and 2-bromo-3-hexylthiophene to the mole of the inorganic base is 1-1.5:1-1.5.

[0032] In some embodiments of the present invention, the ratio of the total mole of 2-bromo-3-(2-undecanoyloxyethyl)thiophene and 2-bromo-3-hexylthiophene to the mole of the organic acid is 2.5-4.5:1.

[0033] In some embodiments of the present invention, after the reaction is completed, a purification step is further included.

[0034] Another object of the present invention is to provide the use of the long ester chain thiophene copolymer or the long ester chain thiophene copolymer prepared by the preparation method of the long ester chain thiophene copolymer in the preparation of perovskite solar cells.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The 3-(2-undecanoyloxyethyl)thiophene segment in the molecular chain of the long-ester chain thiophene copolymer provided by the present invention contains a long chain and an ester group structure, and the ester group is reactive and can increase the bonding force between the layers of the solar cell; the long chain structure of the 3-(2-undecanoyloxyethyl)thiophene segment and the hexyl structure of 3-hexylthiophene are entangled with each other, which effectively improves the stability of the long-ester chain thiophene copolymer, so that the perovskite solar cell maintains a high energy conversion efficiency during long-term use; the long-ester chain thiophene copolymer provided by the present invention has broad application prospects in the fields of solar cells, electrochromic devices, organic transistors, electromagnetic shielding materials, chemical sensors, etc.

[0037] (2) The molecular structure of the long ester chain thiophene copolymer provided by the present invention contains 3-(2-undecanoyloxyethyl)thiophene chain segments, which can improve the fill factor while maintaining a relatively high variable output circuit voltage and short-circuit current density, thereby effectively improving the energy conversion efficiency, and enabling the perovskite solar cell to maintain a relatively high energy conversion efficiency during long-term use, thereby enabling the unencapsulated perovskite solar cell to maintain long-term stability in the atmospheric environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the H NMR spectrum of the 2-bromo-3-(2-undecanoyloxyethyl)thiophene monomer provided in Example 1.

[0039] Figure 2 This is the H-NMR spectrum of the long ester chain thiophene polymer L1 provided in Example 2. DETAILED DESCRIPTION

[0040] The following will clearly and completely describe the concept of the present invention and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are all conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can all be reagents and materials obtained from commercial channels.

[0041] In the following examples and comparative examples, the content of 3-(2-undecanoyloxyethyl)thiophene segments in the long-ester chain thiophene copolymer was determined by nuclear magnetic resonance, the long-ester chain thiophene copolymer was dissolved in deuterated chloroform, TMS was used as an internal standard, and the measurement temperature was 25°C. The molecular weight or degree of polymerization of the long-ester chain thiophene copolymer was determined by gel permeation chromatography (GPC) with THF as the mobile phase. Among them, HT value represents isotacticity, PDI represents molecular weight distribution index;

[0042] The structural formula of 2-bromo-3-hydroxyethylthiophene is shown below:

[0043] .

[0044] Example 1

[0045] This embodiment provides a 2-bromo-3-(2-undecanoyloxyethyl)thiophene monomer, and the synthesis method thereof is as follows:

[0046] Take a clean, anhydrous and oxygen-free single-mouth bottle, put in a magnetic stirrer, add 2-bromo-3-hydroxyethylthiophene (2mmol), undecanoyl chloride (3mmol), triethylamine (202mg), and chloroform (6mL) into the single-mouth bottle, and react in an ice-water bath for 4h. After the reaction is completed, wash the product with water, take the organic layer, and spin-dry to obtain an oily substance, namely 2-bromo-3-(2-undecanoyloxyethyl)thiophene;

[0047] The structure of 2-bromo-3-(2-undecanoyloxyethyl)thiophene is shown below:

[0048]

[0049] Example 2

[0050] This embodiment provides a long ester chain thiophene copolymer L1, and the synthesis method thereof is as follows:

[0051] Take a clean, anhydrous and oxygen-free reaction bottle, put in a magnetic stirrer, add 2-bromo-3-(2-undecanoyloxyethyl)thiophene (0.05mmol), 2-bromo-3-hexylthiophene (0.45mmol), potassium carbonate (0.75mmol), quinoline imine palladium catalyst C1 (0.25mmol%), pivalic acid (0.15mmol), solvent N,N-dimethylacetamide (4mL) into the reaction bottle, react at 100℃ for 24h under nitrogen atmosphere, and the product is precipitated under 40mL methanol. Precipitation was performed to obtain a random long ester chain thiophene copolymer L1 with a yield of 51%. The random long ester chain thiophene copolymer L1 was characterized by nuclear magnetic resonance and GPC, and the molar percentage of 2-bromo-3-(2-undecanoyloxyethyl)thiophene chain segments in the long ester chain thiophene copolymer chain segments was 6.7%, that is, the copolymerization degree was 6.7 mmol%, the HT value was 80%, the PDI was 3.56, and the number average molecular weight Mn was 12.7 KDa; the structures of the quinoline imine palladium catalyst C1 and the random long ester chain thiophene copolymer L1 are shown below:

[0052]

[0053] Among them, x=6.7mmol%, y=93.3mmol%.

[0054] Example 3

[0055] This embodiment provides a long ester chain thiophene copolymer L2, and the synthesis method thereof is as follows:

[0056] Take a clean, anhydrous and oxygen-free reaction bottle, put in a magnetic stirrer, and add 2-bromo-3-(2-undecanoyloxyethyl)thiophene (0.1mmol), 2-bromo-3-hexylthiophene (0.8mmol), potassium carbonate (0.9mmol), quinoline imine palladium catalyst C1 into the reaction bottle. (0.25mmol%), pivalic acid (0.3mmol), solvent N,N-dimethylacetamide (4mL), under nitrogen atmosphere, react at 100℃ for 20h, the product is precipitated in 40mL methanol to obtain a random long ester chain thiophene copolymer L2 with a yield of 62%. The random long ester chain thiophene copolymer L2 is characterized by nuclear magnetic resonance and GPC, and the molar percentage of 2-bromo-3-(2-undecanoyloxyethyl)thiophene segment in the long ester chain thiophene copolymer segment is 8%, that is, the copolymerization degree is 8mmol%, the HT value is 83%, the PDI is 3.62, and the number average molecular weight Mn is 15.2KDa; the structures of the quinoline imine palladium catalyst C1 and the random long ester chain thiophene copolymer L2 are as follows:

[0057]

[0058] Among them, x=8mmol%, y=92mmol%.

[0059] Example 4

[0060] This embodiment provides a long ester chain thiophene copolymer L3, the synthesis method of which is as follows:

[0061] Take a clean, anhydrous and oxygen-free reaction bottle, put in a magnetic stirrer, and add 2-bromo-3-(2-undecanoyloxyethyl)thiophene (0.15mmol), 2-bromo-3-hexylthiophene (0.85mmol), potassium carbonate (1.5mmol), quinoline imine palladium catalyst C1 into the reaction bottle respectively. (0.125mmol%), pivalic acid (0.25mmol), solvent N,N-dimethylacetamide (4mL), under nitrogen atmosphere, react at 120℃ for 24h, the product is precipitated in 40mL methanol to obtain a random long ester chain thiophene copolymer L3 with a yield of 54%. The random long ester chain thiophene copolymer L3 is characterized by nuclear magnetic resonance and GPC, and the molar percentage of 2-bromo-3-(2-undecanoyloxyethyl)thiophene segment in the long ester chain thiophene copolymer segment is 9.5%, that is, the copolymerization degree is 9.5mmol%, the HT value is 81%, the PDI is 3.67, and the number average molecular weight Mn is 13.3KDa; the structures of the quinoline imine palladium catalyst C1 and the random long ester chain thiophene copolymer L3 are as follows:

[0062]

[0063] Among them, x=9.5mmol%, y=91.5mmol%.

[0064] Example 5

[0065] This embodiment provides a long ester chain thiophene copolymer L4, the synthesis method of which is as follows:

[0066] Take a clean, anhydrous and oxygen-free reaction bottle, put in a magnetic stirrer, and add 2-bromo-3-(2-undecanoyloxyethyl)thiophene (0.1mmol), 2-bromo-3-hexylthiophene (0.9mmol), potassium carbonate (1.5mmol), quinoline imine palladium catalyst C1 into the reaction bottle respectively. (0.2mmol%), pivalic acid (0.5mmol), solvent N,N-dimethylacetamide (4mL), under nitrogen atmosphere, react at 100℃ for 32h, the product is precipitated in 40mL methanol to obtain a random long ester chain thiophene copolymer L4 with a yield of 47%. The random long ester chain thiophene copolymer L4 is characterized by nuclear magnetic resonance and GPC, and the molar percentage of 2-bromo-3-(2-undecanoyloxyethyl)thiophene segment in the long ester chain thiophene copolymer segment is 5%, that is, the copolymerization degree is 5mmol%, the HT value is 80%, the PDI is 3.51, and the number average molecular weight Mn is 9.7KDa; the structures of the quinoline imine palladium catalyst C1 and the random long ester chain thiophene copolymer L4 are as follows:

[0067]

[0068] Among them, x=5mmol%, y=95mmol%.

[0069] Example 6

[0070] This embodiment provides a long ester chain thiophene copolymer L5, and its synthesis method is as follows:

[0071] Take a clean, anhydrous and oxygen-free reaction bottle, put in a magnetic stirrer, and add 2-bromo-3-(2-undecanoyloxyethyl)thiophene (0.08 mmol), 2-bromo-3-hexylthiophene (0.32 mmol), potassium carbonate (0.8 mmol), quinoline imine palladium catalyst C1 into the reaction bottle. (0.3mmol%), pivalic acid (0.24mmol), solvent N,N-dimethylacetamide (4mL), under nitrogen atmosphere, react at 90℃ for 36h, the product is precipitated in 40mL methanol to obtain a random long ester chain thiophene copolymer L5 with a yield of 56%. The random long ester chain thiophene copolymer L5 is characterized by nuclear magnetic resonance and GPC, and the molar percentage of 2-bromo-3-(2-undecanoyloxyethyl)thiophene segment in the long ester chain thiophene copolymer segment is 12%, that is, the copolymerization degree is 12mmol%, the HT value is 85.7%, the PDI is 3.85, and the number average molecular weight Mn is 11.6KDa; the structures of the quinoline imine palladium catalyst C1 and the random long ester chain thiophene copolymer L5 are as follows:

[0072]

[0073] Among them, x=12mmol%, y=88mmol%.

[0074] Example 7

[0075] This embodiment provides a long ester chain thiophene copolymer L6, and the synthesis method thereof is as follows:

[0076] Take a clean, anhydrous and oxygen-free reaction bottle, put in a magnetic stirrer, and add 2-bromo-3-(2-undecanoyloxyethyl)thiophene (0.06mmol), 2-bromo-3-hexylthiophene (0.31mmol), potassium carbonate (0.45mmol), quinoline imine palladium catalyst C1 into the reaction bottle respectively. (0.15mmol%), pivalic acid (0.1mmol), solvent N,N-dimethylacetamide (4mL), under nitrogen atmosphere, react at 130℃ for 20h, the product is precipitated in 40mL methanol to obtain a random long ester chain thiophene copolymer L6 with a yield of 58%. The random long ester chain thiophene copolymer L6 is characterized by nuclear magnetic resonance and GPC, and the molar percentage of 2-bromo-3-(2-undecanoyloxyethyl)thiophene segment in the long ester chain thiophene copolymer segment is 10.5%, that is, the copolymerization degree is 10.5mmol%, the HT value is 82%, the PDI is 3.73, and the number average molecular weight Mn is 12.1KDa; the structures of the quinoline imine palladium catalyst C1 and the random long ester chain thiophene copolymer L6 are as follows:

[0077]

[0078] Among them, x=10.5mmol%, y=89.5mmol%.

[0079] Example 8

[0080] This embodiment provides a long ester chain thiophene copolymer L7, and its synthesis method is as follows:

[0081] Take a clean, anhydrous and oxygen-free reaction bottle, put in a magnetic stirrer, and add 2-bromo-3-(2-undecanoyloxyethyl)thiophene (0.15mmol), 2-bromo-3-hexylthiophene (0.85mmol), potassium carbonate (0.6mmol), quinoline imine palladium catalyst C1 into the reaction bottle respectively. (0.4mmol%), pivalic acid (0.16mmol), solvent N,N-dimethylacetamide (4mL), under nitrogen atmosphere, react at 120℃ for 32h, the product is precipitated in 40mL methanol to obtain a random long ester chain thiophene copolymer L7 with a yield of 70%. The random long ester chain thiophene copolymer L7 is characterized by nuclear magnetic resonance and GPC. The molar percentage of 2-bromo-3-(2-undecanoyloxyethyl)thiophene chain segments in the long ester chain thiophene copolymer chain segments is 9.4%, that is, the copolymerization degree is 9.4mmol%, the HT value is 80.9%, the PDI is 3.67, and the number average molecular weight Mn is 14.6KDa. The structures of the quinoline imine palladium catalyst C1 and the random long ester chain thiophene copolymer L7 are as follows:

[0082]

[0083] Among them, x=9.4mmol%, y=90.6mmol%.

[0084] Example 9

[0085] This embodiment provides a long ester chain thiophene copolymer L8, and its synthesis method is as follows:

[0086] Take a clean, anhydrous and oxygen-free reaction bottle, put in a magnetic stirrer, and add 2-bromo-3-(2-undecanoyloxyethyl)thiophene (0.35mmol), 2-bromo-3-hexylthiophene (1.76mmol), potassium carbonate (3.2mmol), quinoline imine palladium catalyst C1 into the reaction bottle. (1.2mmol%), pivalic acid (0.9mmol), solvent N,N-dimethylacetamide (8mL), under nitrogen atmosphere, react at 110℃ for 18h, the product is precipitated in 40mL methanol to obtain a random long ester chain thiophene copolymer L8 with a yield of 65%. The random long ester chain thiophene copolymer L8 is characterized by nuclear magnetic resonance and GPC. The molar percentage of 2-bromo-3-(2-undecanoyloxyethyl)thiophene chain segments in the long ester chain thiophene copolymer chain segments is 14.7%, that is, the copolymerization degree is 14.7mmol%, the HT value is 87%, the PDI is 3.86, and the number average molecular weight Mn is 10.9KDa; the structures of the quinoline imine palladium catalyst C1 and the random long ester chain thiophene copolymer L8 are as follows:

[0087]

[0088] Among them, x=14.7mmol%, y=85.3mmol%.

[0089] Example 10

[0090] This embodiment provides a long ester chain thiophene copolymer L9, and the synthesis method thereof is as follows:

[0091] Take a clean, anhydrous and oxygen-free reaction bottle, put in a magnetic stirrer, and add 2-bromo-3-(2-undecanoyloxyethyl)thiophene (0.06mmol), 2-bromo-3-hexylthiophene (0.42mmol), potassium carbonate (0.5mmol), quinoline imine palladium catalyst C1 into the reaction bottle respectively. (0.48mmol%), pivalic acid (0.12mmol), solvent N,N-dimethylacetamide (4mL), under nitrogen atmosphere, at 100℃ for 36h, the product was precipitated in 40mL methanol to obtain a random long ester chain thiophene copolymer L9 with a yield of 63%. The random long ester chain thiophene copolymer L9 was characterized by nuclear magnetic resonance and GPC. The molar percentage of 2-bromo-3-(2-undecanoyloxyethyl)thiophene chain segments in the long ester chain thiophene copolymer chain segments was 7.5%, that is, the copolymerization degree was 7.5mmol%, the HT value was 80.2%, the PDI was 3.58, and the number average molecular weight Mn was 14.8KDa. The structures of the quinoline imine palladium catalyst C1 and the random long ester chain thiophene copolymer L9 are shown below:

[0092]

[0093] Among them, x=7.5mmol%, y=92.5mmol%.

[0094] Embodiment 11

[0095] This embodiment provides a long ester chain thiophene copolymer L10, the synthesis method of which is as follows:

[0096] Take a clean, anhydrous and oxygen-free reaction bottle, put in a magnetic stirrer, add 2-bromo-3-(2-undecanoyloxyethyl)thiophene (0.24mmol), 2-bromo-3-hexylthiophene (1.08mmol), potassium carbonate (1.5mmol), quinoline imine palladium catalyst C1 (1.62mmol%), pivalic acid (0.36mmol), solvent N, N-dimethylacetamide (8mL) into the reaction bottle, react at 130℃ for 48h under nitrogen atmosphere, and the product is precipitated under 40mL methanol. The random long ester chain thiophene copolymer L9 was obtained by precipitation with a yield of 75%. The random long ester chain thiophene copolymer L9 was characterized by nuclear magnetic resonance and GPC. The molar percentage of 2-bromo-3-(2-undecanoyloxyethyl)thiophene chain segments in the long ester chain thiophene copolymer chain segments was 11.8%, that is, the copolymerization degree was 11.8 mmol%, the HT value was 84.5%, the PDI was 3.82, and the number average molecular weight Mn was 17.3 KDa. The structures of the quinoline imine palladium catalyst C1 and the random long ester chain thiophene copolymer L10 are shown below:

[0097]

[0098] Among them, x=11.8mmol%, y=88.2mmol%.

[0099] Comparative Example 1

[0100] This embodiment provides a poly (3-hexylthiophene) L11, and its synthesis method is as follows:

[0101] A clean, anhydrous and oxygen-free reaction bottle was taken, a magnetic stirrer was placed, 2-bromo-3-hexylthiophene (1 mmol), potassium carbonate (1.5 mmol), quinoline imine palladium catalyst C1 (0.5 mmol%), pivalic acid (0.36 mmol), and solvent N, N-dimethylacetamide (4 mL) were added to the reaction bottle respectively, and the reaction was carried out at 120 ° C for 24 h under a nitrogen atmosphere. The product was precipitated in 40 mL of methanol to obtain poly (3-hexylthiophene) L11 with a yield of 87%. Poly (3-hexylthiophene) L11 was characterized by nuclear magnetic resonance and GPC, and the PDI was 2.45 and the number average molecular weight Mn was 15.9 KDa; the structures of the quinoline imine palladium catalyst C1 and poly (3-hexylthiophene) L11 are shown as follows:

[0102] .

[0103] Comparative Example 2

[0104] Take a clean, anhydrous and oxygen-free reaction bottle, put in a magnetic stirrer, add 2-bromo-3-(2-undecanoyloxyethyl)thiophene (0.4mmol), anhydrous potassium carbonate (0.56mmol), pivalic acid (0.8mmol) and 4mL of N,N-dimethylacetamide as solvent, then add quinoline imine palladium catalyst C1 (0.25mmol%), and heat to 120°C under natural conditions. o C, control the temperature and stir to react for 24 hours, stop heating, and add 40 mL of methanol for precipitation. No product is precipitated. The structure of quinoline imine palladium catalyst C1 is shown below:

[0105]

[0106] Example 12

[0107] The present invention provides a pin-type perovskite solar cell, wherein the specific cell structure is ITO / long ester chain thiophene copolymer / perovskite active layer / PCBM / BCP / Ag, and the specific implementation steps are as follows:

[0108] (1) Cleaning of the transparent substrate layer: First, take out the ITO transparent conductive glass, tear off the plastic protective film on the surface, and first use detergent to gently wipe the surface oil and dirt, and then ultrasonically clean it in a 0.2wt% detergent aqueous solution, deionized water, and isopropanol for 15 minutes respectively. Finally, use nitrogen to blow dry the isopropanol on the ITO surface and put it in a box for later use.

[0109] (2) Deposition of hole transport layer: The long ester chain thiophene copolymer of Example 2 was prepared into a precursor solution of 0.2 mg / mL, and the solvent was chlorobenzene. The cleaned ITO was first placed in an ultraviolet ozone cleaner for surface hydrophilic treatment, and then the precursor solution was sucked out with a pipette and evenly covered on the ITO surface. The solvent was dried by spin coating (500 rpm / min, 3 s; 3000 rpm / min, 20 s).

[0110] (3) Preparation of wetting layer: The purchased aluminum oxide nanoparticle (<50 nm) dispersion (20%) was mixed with isopropanol at a volume ratio of 1:50 (aluminum oxide dispersion: isopropanol) to prepare an aluminum oxide precursor solution. The prepared aluminum oxide precursor solution was then aspirated with a pipette and evenly covered on the surface of the hole transport layer. The solvent was dried by spin coating (100 rpm / min, 3 s; 5000 rpm / min, 20 s).

[0111] (4) Preparation of perovskite active layer: The FAPbI3 system perovskite precursor solution (1000 rpm / min, 3s; 5000 rpm / min, 30s, 100 μL chlorobenzene was added as anti-solvent at 21s) was aspirated with a pipette and evenly covered on the surface of the wetting layer to form a perovskite active layer, and then annealed on a hot stage at 100°C for 30-60 min.

[0112] (5) Deposition of electron transport layer: Weigh 20 mg of PCBM and add 1 mL of chlorobenzene to prepare the precursor solution of the electron transport layer. The electron transport layer precursor solution was deposited on the surface of the perovskite active layer by spin coating (500 rpm / min, 3 s; 2500 rpm / min, 20 s).

[0113] (6) Deposition of hole blocking layer: 8 mg of BCP was weighed and 16 mL of isopropanol was added to prepare a precursor solution. The prepared precursor solution was then aspirated with a pipette and evenly covered on the surface of the hole blocking layer. The solvent was dried by spin coating (100 rpm / min, 3 s; 5000 rpm / min, 20 s).

[0114] (7) Deposition of metal electrode layer: A 100 nm thick Ag film was thermally evaporated under high vacuum at an evaporation rate of 0.3 Å / s for 20 nm and then deposited on the surface of the hole blocking layer at 1 Å / s to a thickness of 100 nm.

[0115] Examples 13 to 21 and Comparative Example 3

[0116] The present invention provides a pin-type perovskite solar cell, which is different from Example 12 in that the "long ester chain thiophene copolymer of Example 2" mentioned in point (2) of Example 11 is replaced by "long ester chain thiophene copolymers of Examples 3 to 11 or poly (3-hexylthiophene) of Comparative Example 1", respectively, to obtain the pin-type perovskite solar cells of Examples 13 to 21 and Comparative Example 3.

[0117] The performance of the pin-type perovskite solar cells of Examples 12 to 21 and Comparative Example 3 was tested. The test method is as follows, and the results are shown in Table 1.

[0118] (1) JV characteristic curve: The JV characteristic curve of the device was measured using a Keithley 2440 light source under a simulated AM1.5G spectrum.

[0119] The light intensity was calibrated using a solar simulator (Newport, 91160) from NREL using a standard silicon solar cell device. The effective measurement area was 0.07 cm 2, under reverse and forward bias scans, the scan rate was 100mV / s and the bias range was from -0.2V to 1.2V.

[0120] Table 1. Performance of perovskite solar cells of Examples 12 to 21 and Comparative Example 3.

[0121] sample Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) Example 12 0.96 21.94 80.74 17.01 Example 13 0.98 22.36 81.54 17.86 Embodiment 14 0.92 22.48 82.59 17.08 Embodiment 15 0.94 22.57 82.62 17.52 Example 16 0.95 22.61 81.34 17.47 Embodiment 17 0.93 22.34 83.13 17.31 Embodiment 18 0.94 21.73 83.08 16.96 Embodiment 19 0.96 22.49 82.30 17.76 Embodiment 20 0.97 22.58 80.25 17.57 Embodiment 21 1.00 21.82 80.98 17.67 Comparative Example 3 0.97 21.07 55.95 11.43

[0122] As can be seen from Table 1, the long ester chain thiophene copolymers prepared in Examples 2 to 11 of the present invention are used to prepare perovskite solar cells, which can improve the fill factor while maintaining a relatively high variable output circuit voltage and short-circuit current density, thereby effectively improving the energy conversion efficiency.

[0123] The unpackaged pin-type perovskite solar cells of Examples 12 to 21 and Comparative Example 3 were stored in an atmospheric environment for 30 days and then subjected to performance testing. The results are shown in Table 2.

[0124] Table 2. Performance of perovskite solar cells of Examples 12 to 21 and Comparative Example 3.

[0125] sample PCE(%) Example 12 15.85 Example 13 16.56 Embodiment 14 15.93 Embodiment 15 16.28 Example 16 16.12 Embodiment 17 16.11 Embodiment 18 15.77 Embodiment 19 16.49 Embodiment 20 16.30 Embodiment 21 16.21 Comparative Example 3 7.84

[0126] It can be seen from Table 1 and Table 2 that the long ester chain thiophene copolymers prepared in Examples 2 to 11 of the present invention are used to prepare perovskite solar cells, which can improve the fill factor while maintaining a relatively high variable output circuit voltage and short-circuit current density, thereby effectively improving the energy conversion efficiency, and can enable the perovskite solar cell to maintain a relatively high energy conversion efficiency during long-term use, so that the unpackaged perovskite solar cell can also maintain stability for a long time in the atmospheric environment.

[0127] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A long ester chain thiophene copolymer, characterized in that: The long ester chain thiophene copolymer is a copolymer of 3-hexylthiophene and 3-(2-undecanoyloxyethyl)thiophene, and the molar percentage of the 3-(2-undecanoyloxyethyl)thiophene chain segment in the long ester chain thiophene copolymer chain segment is 5-15%.

2. The long ester chain thiophene copolymer according to claim 1, characterized in that: The molar percentage of the 3-(2-undecanoyloxyethyl)thiophene chain segment to the long ester chain thiophene copolymer chain segment is 5-10%.

3. The long ester chain thiophene copolymer according to claim 1, characterized in that: The molar percentage of the 3-(2-undecanoyloxyethyl)thiophene chain segment to the long ester chain thiophene copolymer chain segment is 12-15%.

4. The long ester chain thiophene copolymer according to claim 1, characterized in that: The long ester chain thiophene copolymer is a random copolymer.

5. The long ester chain thiophene copolymer according to claim 1, characterized in that: The structure of the long ester chain thiophene copolymer is shown in formula (I): Formula (I) Wherein, the number average molecular weight of the long ester chain thiophene copolymer is 9.7~17.3KDa.

6. The long ester chain thiophene copolymer according to claim 1, characterized in that: The HT value of the long ester chain thiophene copolymer is ≥80%, and the PDI is ≥3.

5.

7. A method for preparing a long ester chain thiophene copolymer, characterized in that: The steps include: Under the catalysis of a palladium catalyst, 2-bromo-3-(2-undecanoyloxyethyl)thiophene and 2-bromo-3-hexylthiophene react to obtain the long ester chain thiophene copolymer according to any one of claims 1 to 6.

8. The method for preparing a long ester chain thiophene copolymer according to claim 7, characterized in that: The palladium catalyst is selected from a quinoline imine palladium catalyst, and the structure of the quinoline imine palladium catalyst is shown in formula (II): Formula (II); and / or, the molar ratio of 2-bromo-3-(2-undecanoyloxyethyl)thiophene to 2-bromo-3-hexylthiophene is 1-3:7-9; and / or, the ratio of the total mole of the 2-bromo-3-(2-undecanoyloxyethyl)thiophene and 2-bromo-3-hexylthiophene to the mole of the palladium catalyst is 1:0.001-0.05; And / or, the reaction temperature is 90-130° C. and the reaction time is 12-48 hours.

9. The method for preparing a long ester chain thiophene copolymer according to claim 7, characterized in that: The reaction further comprises an inorganic base, an organic acid and a solvent; the inorganic base comprises at least one of potassium carbonate and sodium carbonate; And / or, the organic acid includes at least one of pivalic acid and caproic acid; and / or, the solvent comprises N,N-dimethylacetamide; and / or, the ratio of the total mole of 2-bromo-3-(2-undecanoyloxyethyl)thiophene and 2-bromo-3-hexylthiophene to the mole of the inorganic base is 1-1.5:1-1.5; And / or, the ratio of the total mole of 2-bromo-3-(2-undecanoyloxyethyl)thiophene and 2-bromo-3-hexylthiophene to the mole of the organic acid is 2.5-4.5:

1.

10. Use of the long ester chain thiophene copolymer according to any one of claims 1 to 6 or the long ester chain thiophene copolymer prepared by the preparation method of the long ester chain thiophene copolymer according to any one of claims 7 to 9 in the preparation of perovskite solar cells.

Citation Information

Patent Citations

  • A soluble thiophene copolymer, its preparation method and application

    CN110218298B

  • Ester thiophene-hexylthiophene copolymer as well as preparation method and application thereof

    CN119019651A